OPTICAL COHERENCE TOMOGRAPHY BASELINE PREDICTORS FOR INITIAL BEST-CORRECTED VISUAL ACUITY RESPONSE TO INTRAVITREAL ANTI-VASCULAR ENDOTHELIAL GROWTH FACTOR TREATMENT IN EYES WITH DIABETIC MACULAR EDEMA: The CHARTRES Study. Issue 6 (June 2018) - Santos, Ana R.; Costa, Miguel Â.; Schwartz, Christian; Alves, Dalila; Figueira, João; Silva, Rufino; Cunha-Vaz, Jose G.
Abstract : Purpose: To identify baseline optical coherence tomography morphologic characteristics predicting the visual response to anti-vascular endothelial growth factor therapy in diabetic macular edema. Methods: Sixty-seven patients with diabetic macular edema completed a prospective, observational study (NCT01947881-CHARTRES). All patients received monthly intravitreal injections of Lucentis for 3 months followed by PRN treatment and underwent best-corrected visual acuity measurements and spectral domain optical coherence tomography at Baseline, Months 1, 2, 3, and 6. Visual treatment response was characterized as good (≥10 letters), moderate (5–10 letters), and poor (<5 or letters loss). Spectral domain optical coherence tomography images were graded before and after treatment by a certified Reading Center. Results: One month after loading dose, 26 patients (38.80%) were identified as good responders, 19 (28.35%) as Moderate and 22 (32.83%) as poor responders. There were no significant best-corrected visual acuity and central retinal thickness differences at baseline ( P = 0.176; P = 0.573, respectively). Ellipsoid zone disruption and disorganization of retinal inner layers were good predictors for treatment response, representing a significant risk for poor visual recovery to anti-vascular endothelial growth factor therapy (odds ratio = 10.96; P < 0.001 for ellipsoid zone disruption and odds ratio = 7.05; P = 0.034 for disorganization of retinal inner layers). Conclusion: Damage of ellipsoid zone, higher values of disorganization of retinal inner layers, and central retinal thickness decrease are good predictors of best-corrected visual acuity response to anti-vascular endothelial growth factor therapy. Abstract : Resolution of diabetic macular edema is not always followed by visual function recovery. Identification of baseline characteristics predictable of different visual outcomes of anti-vascular endothelial growth factor therapy would be useful for treatment management.The authors' results revealed that ellipsoid zone disruption and higher disorganization of retinal inner layer values are predictors of poor response to treatment.